Correlation Between Ultrasonography BI-RADS Classification and Histopathological Examination on Breast Tumor Patients in Gorontalo - Purnomo, Frederick Johan; Kurniawan, Benny Nanda; Pranoto, Agung Sindu (Syntax Literate, 2025)
Breast cancer remains one of the leading causes of cancer-related mortality among women worldwide. Early and accurate diagnosis is crucial for improving survival rates, particularly in regions with limited access to advanced diagnostic facilities. The ultrasound (USG) examination with Breast Imaging Reporting and Data System (BI-RADS) classification standardizes breast imaging interpretation and aids in risk stratification. However, its correlation with histopathological outcomes requires further evaluation. This study aims to analyze the correlation between ultrasonographic BI-RADS classifications and histopathological findings in patients with breast tumors in Gorontalo. This study is a multicentre retrospective observational analytic with a cross-sectional approach conducted at four hospitals in Gorontalo, Indonesia. The study included patients who underwent breast ultrasonography with BI-RADS categories 3, 4, or 5, followed by histopathological confirmation between January 2023 and January 2025. The results show 75 patients, 25 (33.3%) were classified as BI-RADS category 3, 26 (34.7%) as BI-RADS category 4, and 24 (32%) as BI-RADS category 5. Histopathological examination revealed that 92% of BI-RADS 3, 53.8% of BI-RADS 4, and 8.4% of BI-RADS 5 cases were benign, while 8% of BI-RADS category 3, 46.2% of BI-RADS category 4, and 91.6% of BI-RADS category 5 were confirmed as malignant. The chi-squared test demonstrated a significant correlation between BI-RADS classifications and histopathological findings (p < 0.001). Thus, the study confirms the strong correlation between ultrasonographic BI-RADS classifications and histopathological outcomes, emphasizing its reliability in breast cancer evaluation.